(untitled) (Sciences & Technologie. C, Biotechnologies, 2006)
Two Tunisian barley varieties,Martin and Rihane, differing in degrees of adaptation to environmental conditions, were grown under different treatments ofnitrogen (N) fertilization. Total nitrogen content increased when intensifying N supply whereas grain and albumen weights decreased. Effect of N fertilization on storage protein components (expressed in mg per albumen) was determined by Nu-PAGE electrophoresis system using the MOBS running buffer and densitometry analysis. The effect of N supply on the change of B-hordein fraction and some amino acids (AA) particularly the cysteine, implicates in disulfide bonds of protein aggregates, was discussed in relation to different degrees of adaptability toenvironmental conditions which characterize each barley variety.